Acute phase proteins, heat shock protein and other blood parameters as physiological indicators of stress in poultry - Najafi, Pardis (2016)
Experiments were conducted to explore physiological aspect of stress in chickens. Acute phase proteins (APPs), heat shock protein (HSP) 70 and other blood parameters responses to various stressors were investigated. Activation of APPs by nonpathogenic stimulus is still unclear in poultry species. Thus, this research was conducted to elucidate the relationship between stress and APPs response in poultry. In Chapter 3, an experiment was conducted to determine the effect of corticosterone (CORT) administration on serum ovotransferrin (OVT), α1-acid glycoprotein (AGP), ceruloplasmin (CP), and IL-6 concentrations, and brain heat shock protein (HSP) 70 expression in broiler chickens. From 14 to 20 day (d) of age, equal numbers of birds were subjected to either (i) daily intramuscular injection with CORT in ethanol:saline (1:1, vol/vol) at 6 mg/kg of BW, or (ii) daily intramuscular injection with 0.5 mL ethanol:saline (1:1, vol/vol; control). Blood samples were collected before CORT treatment (14 d old), 3 and 7 d after CORT injections, and 4 d after cessation of CORT administration for determination of serum levels of CORT, OVT, AGP, CP, and IL-6. Brain samples (whole cerebrum) were collected to measure HSP70 density. Although CORT administration significantly increased feed intake, weight gain was significantly decreased. Administration of CORT also increased CORT, OVT, CP, AGP, IL-6, and HSP70 expression. Four days following cessation of CORT administration, OVT declined to the basal level but not CP and AGP. An elevation in CORT can induce an APR and HSP70 expression. In Chapter 4, effect of feed deprivation on serum CORT, OVT, AGP and CP concentrations in broiler chickens was investigated. At 21 days of age, birds were subjected to one of five feed deprivation periods: (i) 0 h (ad libitum) (AL), (ii) 6 h, (iii) 12 h, (iv) 18 h, (v) 24 h, and (vi) 30 h. Upon completion of the deprivation period, blood samples were collected to determine CORT, OVT, AGP and CP. Results showed that feed deprivation for 24 h or more caused a marked elevation in CORT when compared to AL. However, significant increases in AGP, CP and OVT were only noted following 30 h of feed deprivation. Thus, elicitation of AGP, CP and OVT response may represent a more chronic stressful condition than CORT response in assessing the well-being of broilers. In Chapter 5, effect of different stocking densities on serum CORT, OVT, AGP and CP concentrations, brain HSP70 expression and performance in broiler chickens exposed to unheated and heated conditions was determined. Day-old chicks were stocked at 0.100m2/bird (low density (LD)) or 0.063m2/ bird (high density (HD)), in battery cages and housed in environmentally controlled rooms. From 21 to 35 days of age, birds from each stocking density group were exposed to either 24 or 32 °C. Growth performance was recorded during the heat treatment period, and blood and brain samples were collected to determine CORT, OVT, AGP, CP and HSP70 levels on day 35. Heat treatment but not stocking density was detrimental to growth performance. There were significant temperature×density interactions for CORT, CP and OVT on day 35. Although HD elevated CORT, CP and OVT when compared to LD, the effects of the former were more obvious under heated condition. Both temperature and density had significant effect on AGP and HSP70. In conclusion, irrespective of temperature, high stocking density was physiologically stressful to broiler chickens, as indicated by CORT, AGP, CP, OVT and HSP70, but not detrimental to growth performance and survivability. So AGP, CP and OVT could be useful biomarkers to determine the effect of overcrowding and high temperature on the welfare of broiler chickens. In Chapter 6, an experiment was conducted to determine the physiological response to feed restriction in female broiler breeders using a range of conventional and novel indicators. One hundred female breeders were subjected to one of five feeding regimens from d 28-42 as follows (i) ad libitum feeding (AL), (ii-v) 75, 60, 45 and 30% of ad libitum feed intake. Blood heterophil to lymphocyte ratio (HLR), and plasma circulating CORT, ghrelin (GHR), serotonin (5-HT) and dopamine (DA), and serum acute phase proteins (APP) concentrations, and brain HSP70 level were measured. The results showed a significant effect of feed restriction on blood HLR and plasma CORT, GHR, 5-HT, DA and brain HSP70 levels. However, feed restriction had no effect on serum levels of APP such as AGP, OVT and CP. Serum levels of 5-HT and GHR varied curvilinearly with the feed restriction level. The relationship between brain HSP70 and level of feed restriction was negligible. However, significant linear relationships between HLR, CORT, DA and level of feed restriction were noted. Thus, these three parameters appear to represent a straight forward relation with severity of feed restriction. In Chapter 7, the effect of inhibiting adrenal steroidogenesis on serum CORT, OVT, AGP and CP, IL-6 concentrations and brain HSP70 expression was elucidated in broiler chickens subjected to feed deprivation for 24 hours. On days 4, 5, and 6, equal numbers of birds were assigned to either ad libitum feeding (AL) or (2) 60% of ad libitum feed intake (60FR). On day 35, equal number of AL and 60FR birds were subjected to (i) ad libitum feeding (ALF), (ii) 48 h feed restriction (SFR), or (iii) 24 hours feed restriction with intramuscular injection of 1,1-bis(4-chlorophenyl)-2,2,2-trichloroethane (DDT) (an adrenal blocker) dissolved in corn oil at 100 mg/kg BW (SFR+DDT). The birds were injected with DDT 12 h prior to feed deprivation. Following feed withdrawal, samples were collected to determine CORT, OVT, AGP, CP, IL-6 and HSP70 levels. The earlier feeding regimen had no significant effect on CORT, AGP, OVT, CP, IL-6 and brain HSP70 concentration on day 36. The CORT, AGP, OVT, CP, IL-6 and brain HSP70 density of SFR birds following 24 h (day 36) of feed deprivation were significantly higher than their ALF and SFR+DDT counterparts. However, both ALF and SFR+DDT birds had similar values. It can be concluded that stress without concurrent elevation in the circulating level of corticosterone may not elicit APP, IL-6 and HSP 70 reactions. The linear relationship between DA and level of feed restriction suggests that this neurotransmitter is a potential marker of stress magnetite in feed restricted breeders. Serum levels of 5-HT and GHR are not clear indicators of feed restriction level.